2020
DOI: 10.37865/jafe.2020.0022
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of field performances between two typical mini combine harvesters in grain corn production

Abstract: A mini combine harvester was efficiently designed and developed to harvest grain corn on a small scale farm in order to reduce manpower and operating time as delayed harvesting leads to grain loss. Two typical mini combine harvesters namely Kubota DC105X (KDC) and World Star 7.0Plus (WS) have been introduced to farmers as high output, low fuel consumption and ease of maintenance in grain corn production. This research was undertaken to evaluate and compare the field performance of KDC and WS mini combine harv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
5

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 9 publications
(13 reference statements)
1
3
5
Order By: Relevance
“…Plot 3 had a higher FS value of 2.47 km/h than Plots 2 and 1, which have FS values of 2.38 km/h and 2.40 km/h, respectively, indicating that Plot 3 had 3.8 and 2.9% higher TFC than Plots 2 and 1, respectively. The result of FS in this study is lower than the results reported by Elsoragaby et al (2019) and Masroon et al (2020b) but higher than the result reported by Amponsah et al (2017). It also agrees with the results reported by Masroon et al (2020a), who also reported a moderate FS of 2.55 km/h and stated that when harvesting with a medium-sized combine harvester, a Note.…”
Section: Field Speed and Theoretical Field Capacitysupporting
confidence: 88%
See 3 more Smart Citations
“…Plot 3 had a higher FS value of 2.47 km/h than Plots 2 and 1, which have FS values of 2.38 km/h and 2.40 km/h, respectively, indicating that Plot 3 had 3.8 and 2.9% higher TFC than Plots 2 and 1, respectively. The result of FS in this study is lower than the results reported by Elsoragaby et al (2019) and Masroon et al (2020b) but higher than the result reported by Amponsah et al (2017). It also agrees with the results reported by Masroon et al (2020a), who also reported a moderate FS of 2.55 km/h and stated that when harvesting with a medium-sized combine harvester, a Note.…”
Section: Field Speed and Theoretical Field Capacitysupporting
confidence: 88%
“…The effective harvesting time is accounted for 56.40% of glutinous rice fields' total combine harvester operation time. Masroon et al (2020a) and Masroon et al (2020b) reported that the harvesting time of 2.14 h/ ha and 2.68 h/ha, respectively, which are 13.55 and 30.97% greater than the harvesting time recorded in this study. In another study, Elsoragaby et al (2019) obtained 1.36 h/ ha, 26.50% less than the time recorded in this study.…”
Section: Time Distribution For Harvesting Operationcontrasting
confidence: 68%
See 2 more Smart Citations
“…Where PR stands for power requirements (kW), fu stands for fuel consumption (l/h), ρf stands for fuel density (0.85 kg/l for diesel), LCV stands for the fuel's lower calorific value (10000 kcal/kg), 427 stands for the thermo-mechanical equivalent (J/kcal), ηth stands for the engine thermal efficiency (approximately 35% for diesel engines), and ηmec stands for the engine mechanical efficiency (approximately 80% for diesel engines). The specific energy (SE) was calculated according to Equation 5 [25] as follows:…”
Section: Quantificationsmentioning
confidence: 99%